Active site diversification of P450cam with indole generates catalysts for benzylic oxidation reactions - Kelly, Paul P.; Eichler, Anja; Herter, Susanne; Kranz, David C.; Turner, Nicholas J.; Flitsch, Sabine L. (Beilstein Journal of Organic Chemistry, 2015)
Cytochrome P450 monooxygenases are useful biocatalysts for C–H activation, and there is a need to expand the range of these enzymes beyond what is naturally available. A panel of 93 variants of active self-sufficient P450cam[Tyr96Phe]-RhFRed fusion enzymes with a broad diversity in active site amino acids was developed by screening a large mutant library of 16,500 clones using a simple, highly sensitive colony-based colorimetric screen against indole. These mutants showed distinct fingerprints of activity not only when screened in oxidations of substituted indoles but also for unrelated oxidations such as benzylic hydroxylations.
Keywords: active site mutagenesis; biotransformation; C–H activation; cytochrome P450cam monooxygenase; hydroxylation

(untitled) - Breuer, M.; Ditrich, T.; Habicher, T.; Hauer, B.; Keßeler, M.; Stürmer, R.; Zelinski, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Schulz, S.; Girhard, M.; Urlacher, V. B. (ChemCatChem, 2012)

(untitled) - Filipovic, D.; Paulsen, M. D.; Loida, P. J.; Sligar, S. G.; Ornstein, R. L. (Biochem. Biophys. Res. Commun., 1992)

(untitled) - Jin, S.; Makris, T. M.; Bryson, T. A.; Sligar, S. G.; Dawson, J. H. (J. Am. Chem. Soc., 2003)

(untitled) - Harford-Cross, C. F.; Carmichael, A. B.; Allan, F. K.; England, P. A.; Rouch, D. A.; Wong, L.-L. (Protein Eng., Des. Sel., 2000)

(untitled) - Bell, S. G.; Sowden, R. J.; Wong, L.-L. (Chem. Commun., 2001)

(untitled) - Bell, S. G.; Chen, X. H.; Sowden, R. J.; Xu, F.; Williams, J. N.; Wong, L.-L.; Rao, Z. H. (J. Am. Chem. Soc., 2003)

(untitled) - Sowden, R. J.; Yasmin, S.; Rees, N. H.; Bell, S. G.; Wong, L.-L. (Org. Biomol. Chem., 2005)

(untitled) - Xu, F.; Bell, S. G.; Lednik, J.; Insley, A.; Rao, Z. H.; Wong, L.-L. (Angew. Chem., Int. Ed., 2005)

(untitled) - Çelik, A.; Speight, R. E.; Turner, N. J. (Chem. Commun., 2005)

(untitled) - Manna, S. K.; Mazumadar, S. (Dalton Trans., 2010)

(untitled) - Li, Q.-S.; Schwaneberg, U.; Fischer, P.; Schmid, R. D. (Chemistry, 2000)

(untitled) - Li, H.-m.; Mei, L.-h.; Urlacher, V. B.; Schmid, R. D. (Appl. Biochem. Biotechnol., 2008)

(untitled) - Gillam, E. M. J.; Aguinaldo, A. M. A.; Notley, L. M.; Kim, D.; Mundkowski, R. G.; Volkov, A. A.; Arnold, F. H.; Souček, P.; De Voss, J. J.; Guengerich, F. P. (Biochem. Biophys. Res. Commun., 1999)

(untitled) - Gillam, E. M. J.; Notley, L. M.; Chai, H.; De Voss, J. J.; Guengerich, F. P. (Biochemistry, 2000)

(untitled) - Park, S.-H.; Kim, D.-H.; Kim, D.; Kim, D.-H.; Jung, H.-C.; Pan, J.-G.; Ahn, T.; Kim, D.; Yun, C.-H. (Drug Metab. Dispos., 2010)

(untitled) - Nodate, M.; Kubota, M.; Misawa, N. (Appl. Microbiol. Biotechnol., 2006)

(untitled) - Robin, A.; Roberts, G. A.; Kisch, J. A.; Sabbadin, F.; Grogan, G.; Bruce, N.; Turner, N. J.; Flitsch, S. L. (Chem. Commun., 2009)

(untitled) - Sabbadin, F.; Hyde, R.; Robin, A.; Hilgarth, E.-M.; Deleune, M.; Flitsch, S.; Turner, N.; Grogan, G.; Bruce, N. C. (ChemBioChem, 2010)

(untitled) - Robin, A.; Köhler, V.; Jones, A.; Ali, A.; Kelly, P. P.; O’Reilly, E.; Turner, N. J.; Flitsch, S. L. (Beilstein J. Org. Chem., 2011)

(untitled) - Loida, P. J.; Sligar, S. G. (Biochemistry, 1993)

(untitled) - Gricman, Ł.; Vogel, C.; Pleiss, J. (Proteins: Struct., Funct., Bioinf., 2015)

(untitled) - Poulos, T. L.; Finzel, B. C.; Howard, A. J. (J. Mol. Biol., 1987)

(untitled) - Gotoh, O. (J. Biol. Chem., 1992)

(untitled) - Reetz, M. T.; Bocola, M.; Carballeira, J. D.; Zha, D.; Vogel, A. (Angew. Chem., Int. Ed., 2005)

(untitled) - Poulos, T. L.; Howard, A. J. (Biochemistry, 1987)

(untitled) - Loida, P. J.; Sligar, S. G. (Protein Eng., Des. Sel., 1993)

(untitled) - Lee, Y.-T.; Glazer, E. C.; Wilson, R. F.; Stout, C. D.; Goodin, D. B. (Biochemistry, 2010)

(untitled) - Schlichtling, I.; Berendzen, J.; Chu, K.; Stock, A. M.; Maves, S. A.; Benson, D. E.; Sweet, R. M.; Ringe, D.; Petsko, G. A.; Sligar, S. G. (Science, 2000)

(untitled) - Poulos, T. L.; Finzel, B. C.; Gunsalus, I. C.; Wagner, G. C.; Kraut, J. (J. Biol. Chem., 1985)

(untitled) - Pochapsky, T. C.; Kazanis, S.; Dang, D. (Antioxid. Redox Signaling, 2010)

(untitled) - Hayashi, T.; Harada, K.; Sakurai, K.; Shimada, H.; Hirota, S. (J. Am. Chem. Soc., 2009)

(untitled) - Hoffmann, G.; Bönsch, K.; Greiner-Stöffele, T.; Ballschmiter, M. (Protein Eng., Des. Sel., 2011)

(untitled) - Omura, T.; Sato, R. (J. Biol. Chem., 1964)

(untitled) - Geier, M.; Braun, A.; Emmerstorfer, A.; Pichler, H.; Glieder, A. (Biotechnol. J., 2012)

(untitled) - Gudiminchi, R. K.; Geier, M.; Glieder, A.; Camattari, A. (Biotechnol. J., 2013)

(untitled) - García-Gallego, S.; Bernardes, G. J. L. (Angew. Chem., Int. Ed., 2014)

(untitled) - Bell, S. G.; Harford-Cross, C. F.; Wong, L.-L. (Protein Eng., Des. Sel., 2001)